Chapter Massimo Quaini e la geografia di avanguardia: dal Marxismo e geografia all'Anarchismo e geografia - de Marcos, Valeria (Territori, 2021)
Trying to understand the world to transform it, Massimo Quaini has introduced new methodological research approaches, giving shape to a geography focused on the real problems of his time. His most translated book, Marxism and geography (1974), has influenced on generations of geographers around the world. However, Quaini went further and, in his scientific life, approached the reading of Elisée Reclus and his anarchist geography. This article highlights the contributions of the most rebellious Italian geographer of his time, Professor Massimo Quaini.